Study On The Application Of Red Dragon Fruit Peel Extract As An Organic Corrosion Inhibitor On Carbon Steel Pipes In Corrosive Mediums Of Seawater And Rainwater With Varying Extraction Temperatures - Prasojo, Ikhwan Mahendra; Nuringsih, Fadhilla Maharani; Hakim, Muhammad Fahmi (Peneliti.net, 2024)
Corrosion cannot be avoided, and its presence is a concern in the chemical industry as it can disrupt processes, mainly because process equipment is commonly made of steel pipes. This necessitates the control of corrosion rates using corrosion inhibitors, whether organic or inorganic. The use of organic inhibitors is more environmentally friendly as it does not produce negative impacts on the environment, requires low costs in procurement, and is simpler in its treatment processes. One potential organic inhibitor is the extract from red dragon fruit peel waste. The extract is obtained through the maceration extraction process using 96% ethanol with temperature variations of 80, 85, and 90 ℃. Subsequently, sample immersion is carried out in seawater and rainwater medium. The results of this research indicate that red dragon fruit peel extract contains flavonoids and saponins that can optimally inhibit the corrosion process at an extraction temperature of 85 ℃. SEM tests show that metal samples immersed in the corrosion medium with the inhibitor have a smoother surface compared to those in the